Effectiveness of ASOD: The Effectiveness of ASOD in Handling Drug Trafficking in the Golden Triangle Area ASOD Results from the Social Construction of ASEAN Countries - zahra zamaya; Syahputri, Adrillia; Shafa Maharani Rimosan, Raisyah; Damayanti, Siti; Margareth Lucia Runtuwene, Marsye; Danti Ayuningtyas, Rietma (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2025)
Abused use of narcotics and dangerous drugs (narcotics) is a condition that has long been experienced by many countries in the world.  Abused drug use can cause danger because it is basically a transnational crime. This is because there is a cycle in drug abuse, including production and distribution activities. Transnational crime is a crime that involves many countries where this crime crosses national boundaries which is feared to threaten regional security. Then the ASEAN Official on Drugs was present to make joint efforts to manage and prevent drug-related problems in the ASEAN region as well as carry out monitoring implementation plans to evaluate all ASEAN programs on steps to manage and prevent drug problems. Therefore, the author wants to provide an overview of how the ASOD international regime handles drug trafficking in the region. In this paper the author uses a qualitative approach method by collecting several journals, the articles of which will be analyzed and included in this paper. Based on the results obtained, the author concludes that the regime is not effective in dealing with drug trafficking activities in the Golden Triangle area.